Transketolase regulates sensitivity to APR-246 in p53-null cells independently of oxidative stress modulation - Julia V. Milne (Nature Portfolio, 2021)
Abstract The prevalence and dire implications of mutations in the tumour suppressor, p53, highlight its appeal as a chemotherapeutic target. We recently showed that impairing cellular antioxidant systems via inhibition of SLC7A11, a component of the system xc − cystine-glutamate antiporter, enhances sensitivity to mutant-p53 targeted therapy, APR-246. We investigated whether this synergy extends to other genes, such as those encoding enzymes of the pentose phosphate pathway (PPP). TKT, one of the major enzymes of the PPP, is allegedly regulated by NRF2, which is in turn impaired by accumulated mutant-p53 protein. Therefore, we investigated the relationship between mutant-p53, TKT and sensitivity to APR-246. We found that mutant-p53 does not alter expression of TKT, nor is TKT modulated directly by NRF2, suggesting a more complex mechanism at play. Furthermore, we found that in p53null cells, knockdown of TKT increased sensitivity to APR-246, whilst TKT overexpression conferred resistance to the drug. However, neither permutation elicited any effect on cells overexpressing mutant-p53 protein, despite mediating oxidative stress levels in a similar fashion to that in p53-null cells. In sum, this study has unveiled TKT expression as a determinant for sensitivity to APR-246 in p53-null cells.